Investigation of Temperature Dependent Multi-Walled Nanotube G and D Doublet Using Pseudo-Voigt Functions. Issue 3 (March 2013) - Freihofer, Gregory; Raghavan, Seetha; Gosztola, David
A pseudo-Voigt (PV) function is used as a representation of the Stoke's phonon frequency distributions for a multi-walled nanotube (MWNT) composite G and D doublet. Variable peak assignments with the PV function have been shown to enhance the resolution of these bands commonly used for characterization of carbon nanotube (CNT) composites. The peak assignment study was applied to an in-situ temperature experiment where the addition of new sub-bands in the G and D doublet was determined to reduce the uncertainty of the Raman characteristics. Fitting the spectrum with five pseudo-Voigt bands was concluded to give the most consistent results, producing the lowest uncertainty values for G-peak position ( v G ) and D/G intensity ratio.